Insights into the Molecular Mechanisms of Purine Compounds Synergistically Inducing Larval Settlement in Mytilopsis sallei Using Multi-Group Comparative Transcriptomic Analysis - Jian He; Huanhuan Hao; Huakang Pan; Shanshan Yao; Yiran Zhao; Shifeng Guo; Jianfang Huang; Danqing Feng (Biology)
Most benthic marine invertebrates exhibit a characteristic biphasic life cycle, consisting of a planktonic larval stage followed by a benthic adult stage [...]